Unraveling the Functional Role of NPF6 Transporters - Wen, Zhengyu; Kaiser, Brent N. (Frontiers in Plant Science, 2018)
The NPF family represents a growing list of putative nitrate permeable transport proteins expressed within multiple cell types and tissues across a diverse range of plant species. Their designation as nitrate permeable and / or selective transporters is slowly being defined as more genes are characterized and their functional activities tested both in planta and in vitro. The most notable of the NPF family has been the Arabidopsis thaliana homolog, AtNPF6;3, previously known as AtNRT1;1 or CHL1. AtNPF6;3 has traditionally been characterized as a dual-affinity nitrate transporter contributing to root nitrate uptake in Arabidopsis. It has also been identified as a nitrate sensor which regulates the expression of high-affinity nitrate transport proteins NRT2s and lateral root development as a part of the primary nitrate response in plants. The sensor function of AtNPF6;3 has also been attributed to its auxin transport activity. Other homologs of AtNPF6;3 are now being described highlighting the variability in their functional capabilities (alternative substrates and kinetics) linking to structural aspects of the proteins. This review focusses on NPF6;3-like transport proteins and the knowledge that has been gained since their initial discovery over two decades ago. The review will investigate from a structural point of view how NPF6;3-like proteins may transport nitrate as well as other ions and what can be learned from structural uniqueness about predicted activities in plants.